Unconscious and implicit bias and microaggressions (Assemble You, 2022)
In this track, we'll discuss unconscious and implicit bias. We'll learn what these terms mean, how they can make an environment discriminatory, and what we can do - and not do - to treat people equally. But let's start by exploring the judgments we all make and how they can lead to unconscious and implicit bias.